Development of PowerPoint Based E-Bookstory Learning Media to Improve Reading Skills of Second Grade Elementary School Students - Nur Azizah Siregar; Zaini Dahlan (FKIP - Universitas Riau, 2026)
Reading is a fundamental skill that supports students in acquiring information, understanding learning materials, and developing thinking abilities. However, the reading skills of second-grade elementary school students remain relatively low due to the limited use of engaging and interactive learning media. This study aimed to develop a PowerPoint-based E-Bookstory learning media to improve students’ reading skills. The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 25 second-grade students of Pelita Private Elementary School. Data were collected through interviews, observations, expert validation sheets, and reading tests (pretest and posttest). The developed media integrated story texts, illustrations, audio narration, animations, and interactive exercises to support reading comprehension and engagement. Validation results showed that the media obtained 83% from media experts and 94% from material experts, with an average feasibility score of 89%, categorized as highly feasible. The effectiveness test revealed a significant improvement in students’ reading skills, with the average pretest score increasing from 50 to 92 in the posttest. The N-Gain value of 0.84 indicated high effectiveness. Therefore, the PowerPoint-based E-Bookstory is feasible, practical, and effective for improving reading skills, learning motivation, and student participation.